Utilization Of Information And Communication Technology As A Learning Promotion On High School - Guswan Putra, Anggih Perian; Mulyanto, Agus Iwan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
The use of digital information and communication technology in the world of education and learning will make it easier for users to provide services and search for information, but can also be used for educational promotional activities that are of appropriate value to users Besides being able to be used as educational developments and strategies and innovations in educational activities, it can also be used as a development of learning management learning materials in the field of economics in tertiary institutions. Direct implementation of learning innovation, and mastery of material can be realized with good feedback between education actors and students in utilizing digital information as a transformation of learning promotion strategies.